Determinants of corporate default: the case of South Africa - Raudzingana, Dzivhuluwani (My University, 2020)
There has been a heightened interest from different stakeholders to understand the main drivers of corporate default and the influence of business cycles on corporate default. There has also been a vast amount of research in trying to understand these drivers of corporate default at the micro and macro levels for both developed and emerging economies. This paper studies and quantifies the contribution of both firm specific and macroeconomic factors to corporate default rates for South African firms, both listed and delisted. The corporate default rate is estimated using Moody’s KMV model and then the estimated corporate default rates are used in the Pooled OLS (POLS), Random Effect (RE) and Fixed Effect (FE) models to assess the effect of both firm specific and macroeconomic factors on corporate defaults. This exercise is done first for all the firms and then for subsamples of listed and delisted firms separately using data for the period 1997 to 2018. The list of explanatory variables investigated included micro factors for size, profitability, leverage, tangibility, growth and liquidity. I also included 3 months T-bill rate and inflation for the macro variables. The finding was that the main drivers of corporate default in the South African economy are not too different from those seen in other countries, especially for listed firms. All the explanatory variables were at least significant according to one of the three panel models for listed firms and displayed the expected coefficient signs. On whether corporate defaults are cyclical or anti-cyclical? The results of this study suggest that corporate defaults are cyclical for all the firms (listed and delisted) even though the effect on delisted firms is lagged
A research report submitted in partial fulfilment of the degree of Master of Commerce (Economic Science) in the School of Economic and Business Sciences, University of the Witwatersrand, 2020